2020
DOI: 10.1101/2020.05.07.083063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust and accurate decoding of hand kinematics from entire spiking activity using deep learning

Abstract: Robustness and decoding accuracy remain major challenges in the clinical translation of intracortical brain-machine interface (BMI) systems. In this work, we show that a signal/decoder co-design methodology (exploiting the synergism between the input signal and decoding algorithm within the design development process) can be used to yield robust and accurate BMI decoding performance. Specifically, through applying this process, we propose the combination of using entire spiking activity (ESA) as the input sign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 91 publications
(145 reference statements)
0
42
0
Order By: Relevance
“…in fewer number of LFP channels) than SUA and MUA. This may suggest that ESA exhibits larger spatial coverage (encompassing smaller and farther neurons), which in turn contains more spiking information and higher interchannel correlation 23 . We also found that the higher LFP interchannel correlation (information redundancy), the quicker the inference performance of spiking activity reaches its plateau.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in fewer number of LFP channels) than SUA and MUA. This may suggest that ESA exhibits larger spatial coverage (encompassing smaller and farther neurons), which in turn contains more spiking information and higher interchannel correlation 23 . We also found that the higher LFP interchannel correlation (information redundancy), the quicker the inference performance of spiking activity reaches its plateau.…”
Section: Discussionmentioning
confidence: 99%
“…receptive field) in the visual cortex of monkeys while receiving various visual stimuli 14 , 15 , 20 – 22 . ESA has also been shown to yield more accurate and robust decoding of hand kinematics compared to SUA and MUA from three monkeys performing different tasks 23 .…”
Section: Introductionmentioning
confidence: 99%
“…To give a very few, non-exhaustive examples: [1,2] investigated the ability of different Local Field Potential (LFP) power bands to decode various movements. In [3], they decoded a hand-reaching task using different time-frequency features of intracortical neural signals, e.g. LFP, Single-Unit Activity (SUA), MUA, Entire Spiking Activity (ESA), using linear and deep learning methods.…”
Section: Class 1: Indirect Decoding Methodsmentioning
confidence: 99%
“…For example, with binary spiking events as input, the best size and temporal placement of time bins could be automatically determined, or even features related to the precise timing of spikes could be learned. It was also recently shown that using the envelope of spiking activity, a continuous signal, followed by feature extraction within a neural network, was able to improve decoding performance [48].…”
Section: Spikesmentioning
confidence: 99%